Adipokines vaspin and omentin as risk markers of disorders of carbo- hydrate metabolism development in overweight and obese patients - Karachentsev, Iurii; Kravchun, Nonna; Misiura, Katerina; Dunaieva, Inna; Alhamid, Mohamad Hussain (My University, 2020)
Important role of fractalkine and omentin in pathogenesis of diabetes mel- litus in obesity was proved. The correlation was established between the adipose tissue accumulation, changes in its endocrine function, development of inflammatory processes in the body, abdominal obesity, insulin resistance and type 2 diabetes mellitus onset.
Keywords: vaspin; omentin; overweight